2017
DOI: 10.15226/2381-2915/3/2/00124
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Preterm Birth among Women Who Delivered Preterm Babies at Bugando Medical Centre, Tanzania

Abstract: BackgroundPreterm birth is the leading cause of infant morbidity and mortality globally. Infants who are born preterm suffer long term health consequences. There only few studies done on risk factors for prematurity in Tanzania. This study aimed to determine the risk factors for preterm birth among women who delivered preterm babies at Bugando Medical Centre in Mwanza, Tanzania. MethodsA matched case-control study was conducted at the Bugando Medical Centre from May to June 2015. A total of 50 women with prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
(18 reference statements)
2
13
0
Order By: Relevance
“…Presence of malaria was associated with PTB as evidenced by the pooled analysis of four studies (AOR 3.08; 95% CI: 2.32-4.10) [42,44,79,83]. The pooled analysis of two studies identified that UTI was significantly associated with PTB (AOR 5.27; 95% CI: 2.98-9.31) [37,64] (Fig. 5).…”
Section: Medical Conditionsmentioning
confidence: 85%
See 4 more Smart Citations
“…Presence of malaria was associated with PTB as evidenced by the pooled analysis of four studies (AOR 3.08; 95% CI: 2.32-4.10) [42,44,79,83]. The pooled analysis of two studies identified that UTI was significantly associated with PTB (AOR 5.27; 95% CI: 2.98-9.31) [37,64] (Fig. 5).…”
Section: Medical Conditionsmentioning
confidence: 85%
“…The pooled effects of four studies illustrated that birth interval less than 24 months was positively associated with PTB (AOR 2.03; 95% CI: 1.57-2.62) [10,57,63,74]. The pooled analyses of four studies (AOR 5.52; 95% CI: 4.32-7.05) [37,38,52,72] and three studies (AOR 5.77, 95% CI 4.27-7.79) [7,38,57] showed that ANC visits < 4 and absence of ANC increased the risk of PTB, respectively. The pooled effects of two studies identified that multiple pregnancy was positively associated with PTB (AOR 3.44; 95% CI: 3.02-3.91) [57,79] (Fig.…”
Section: Reproductive Health Factorsmentioning
confidence: 92%
See 3 more Smart Citations